Organosolv pretreatment on oil palm empty fruit bunch: a case study - Wong, Celine Su Chee (2021)
Organosolv pretreatment has high potential in sustainable energy development by transforming lignocellulosic biomass into biofuels. Meanwhile, various studies have limited attempts in exploring different solvents and catalysts used in pretreatment, while inconclusive approaches still existed in the study of synergistic effects between process factors. Consequently, the objective of this research is to comparatively study and analyse organosolv pretreatment on OPEFB under various parameters, including different types of solvents, catalysts, and process factors (concentration, temperature, time). These parameters were explored for their effects on delignification, cellulose recovery/yield, and sugar yield. Besides, this research also studied the physical and chemical characterization of pretreated OPEFB including changes in structural and morphological, degree of crystallinity, functional group, and thermal stability, through the analysis of SEM, XRD, FTIR, and TGA. Furthermore, the interactive effects between sulphuric acid concentration (0.5 – 2.0 %), reaction temperature (160 – 200 °C), and residence time (30 – 90 min) on Glucose (GLU) recovery and Ethanol Organosolv Lignin (EOL) recovery were analyzed from the Central Composite Design (CCD) model built via Design-Expert software. The findings of this research showed that High Boiling Point (HBP) or Low Boiling Point (LBP) alcohols provided higher pretreatment efficiency compared to other solvents. This similar concept was applied to acid catalyst compared with base catalyst. Other than that, an increase in concentration, temperature, and time contributed positive impacts on the pretreatment efficiency until a certain high limit, wherein the exceeded limit led to adverse impact due to inhibitory product formation, sugar decomposition, and lignin recondensation. For characterisation study, more cracks and porous structures with lower crystallinity index were investigated due to the removal of lignin, hemicellulose, and inorganic elements. Other than that, the outcome of modelling showed that SA concentration provided the greatest influence on both GLU and EOL recoveries compared with reaction temperature and residence time. The optimum process conditions (1.97 % SA; 172 °C; 68 min) predicted a GLU recovery rate of 99.07 %, which was in good agreement with a 100 % GLU recovery rate obtained by Goh, et al. (2011).